Polymer composition with improved resistance to thermal shock

CN122953273APending Publication Date: 2026-10-20TICONA LLC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580021460.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-15
Filing Date
2025-02-28
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

遗憾的是,所有的尝试都没能实现足够高的抗热冲击性以使其能够用于许多EV产品应用中

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

A polymer composition is provided comprising a polymer matrix, an impact modifier, mineral particles, and reinforcing fibers, wherein the impact modifier, mineral particles, and reinforcing fibers are dispersed in the polymer matrix. The polymer matrix comprises a polyarylene sulfide and exhibits a melt flow index of about 500 to about 1,000 g / 10 min. The weight ratio of reinforcing fibers to mineral particles is about 2 or greater. The polymer composition also exhibits a thermal shock resistance value of about 800 or higher.
Need to check novelty before this filing date? Find Prior Art

Description

Related applications

[0001] This application is based on and claims priority to U.S. Provisional Patent Application No. 63 / 565,573, filed March 15, 2024, which is incorporated herein by reference. Background Technology

[0002] Electric vehicles, such as battery electric vehicles, plug-in hybrid electric vehicles, mild hybrid electric vehicles, or full hybrid electric vehicles, typically have an electric powertrain that includes an electric propulsion source (e.g., a battery) and a transmission. High-performance polymer materials are commonly used in various components of electric vehicles, such as high-voltage connectors, power converter housings, battery pack housings, fluid pumps, inverters, busbars, stranded cables, single-inductance conductors, cable crimps, cable ring moldings, quick connectors, tees, interconnects, rails, and seals (e.g., brushless DC seals, battery cell seals, etc.). Many of these components are “embedded” because they are formed by embedding components (e.g., metals) into the polymer composition during the molding process. While this process can create complex parts, the significant differences in the coefficients of thermal expansion of different materials can cause cracking when exposed to temperature variations. Therefore, various attempts have been made to develop high-performance polymer compositions with high thermal shock resistance. Unfortunately, none of these attempts have achieved sufficiently high thermal shock resistance for use in many EV applications.

[0003] Therefore, there is a current demand for polymer compositions that can exhibit high thermal shock resistance for use in various applications such as electric vehicle components. Summary of the Invention

[0004] According to one embodiment of the present invention, a polymer composition is disclosed comprising a polymer matrix, an impact modifier, mineral particles, and reinforcing fibers, wherein the impact modifier, mineral particles, and reinforcing fibers are dispersed in the polymer matrix. The polymer matrix comprises a polyarylene sulfide and exhibits a melt flow index of approximately 500 to approximately 1,000 g / 10 min, as determined according to ASTM D1238-13 under a 2.16 kg load and at 190 °C. The weight ratio of reinforcing fibers to mineral particles is approximately 2 or greater. Furthermore, the polymer composition exhibits a thermal shock resistance value of approximately 800 or greater.

[0005] Other features and aspects of the invention are described in more detail below. Attached Figure Description

[0006] In the remainder of the specification, including the accompanying drawings, a full and practical disclosure of the invention, including the best mode of carrying out the invention as would be apparent to those skilled in the art, is set forth in more detail, wherein:

[0007] Figure 1 An electric vehicle is shown that includes components that may incorporate the polymer compositions disclosed herein;

[0008] Figure 2 An embodiment of a busbar that may include the polymer composition disclosed herein is shown;

[0009] Figure 3 A battery assembly is shown that can employ components that may include the polymer compositions disclosed herein;

[0010] Figure 4 An electronic system is shown that may include components that may incorporate the polymer compositions disclosed herein;

[0011] Figure 5 It shows that it can be included in Figure 4 Current sensors in electronic systems;

[0012] Figure 6 An inverter system that can be present in an electric vehicle is shown, which includes components that can contain polymer compositions disclosed herein;

[0013] Figure 7 This is a perspective view of one embodiment of a connector that may include the polymer composition disclosed herein;

[0014] Figure 8 yes Figure 7 A plan view of the connector, wherein the first connector portion and the second connector portion are detached;

[0015] Figure 9 yes Figure 7 A plan view of the connector, wherein the first connector portion and the second connector portion are joined;

[0016] Figure 10 Examples of components that may include the polymer compositions disclosed herein are shown;

[0017] Figure 11 Other components that may comprise the polymer compositions disclosed herein are shown;

[0018] Figure 12 A low-temperature thermal circuit is shown, which may include components that may incorporate the polymer compositions disclosed herein;

[0019] Figure 13 A high-temperature thermal circuit is shown, which may include components that may incorporate the polymer compositions disclosed herein;

[0020] Figure 14 An embodiment of a water pump that may include the polymer composition disclosed herein is shown; and

[0021] Figures 15 to 18 A sample component that can be used to perform the thermal shock resistance test described herein is shown. Detailed Implementation

[0022] Those skilled in the art will understand that the discussion herein is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the invention.

[0023] In general, the present invention relates to a polymer composition that may comprise a polymer matrix, an impact modifier, mineral particles, and reinforcing fibers, wherein the impact modifier, mineral particles, and reinforcing fibers are dispersed in the polymer matrix, which comprises at least one polyaryl sulfide. By selectively controlling specific components and their relative concentrations, it has been found that the resulting compositions can exhibit improved properties for forming components of electric vehicles, such as battery-powered electric vehicles, fuel cell-powered electric vehicles, plug-in hybrid electric vehicles (PHEVs), mild hybrid electric vehicles (MHEVs), full hybrid electric vehicles (FHEVs), etc. More specifically, the polymer compositions may exhibit thermal shock resistance values ​​of about 800 or higher, about 1000 or higher in some embodiments, about 1200 or higher in some embodiments, about 1500 or higher in some embodiments, about 1800 or higher in some embodiments, about 2000 or higher in some embodiments, and about 3000 or higher in some embodiments. As used herein, a “thermal shock resistance value” is determined according to the tests described below and generally refers to the number of heating cycles that a set of sample components can withstand without visual cracking. Such properties can be achieved even with relatively small thickness values, such as about 4 mm or less, about 0.2 mm to about 3.2 mm in some embodiments, and about 0.4 mm to about 3.0 mm in some embodiments (e.g., 0.8, 1.2, 1.5, 2.5, or 3 mm). The polymer composition also exhibits good flame-retardant properties, as determined by the UL 94 test as described below. For example, for a sample having a thickness as described above (e.g., 1.5 mm), the polymer composition can achieve at least a V-1 rating and typically a V-0 rating.

[0024] While exhibiting good thermal shock resistance and flame retardancy, the composition also demonstrates good flow properties reflected by a relatively high melt flow index, for example, from about 500 g / 10 min to about 1,000 g / 10 min according to ASTM D1238-13 at a temperature of 190°C and a load of 2.16 kg; in some embodiments, from about 550 g / 10 min to about 950 g / 10 min; in some embodiments, from about 600 g / 10 min to about 900 g / 10 min; and in some embodiments, from about 650 g / 10 min to about 850 g / 10 min. The composition also exhibits a relatively low melt viscosity, for example, according to ISO 11443:2021 at a temperature of about 310°C and a melt flow index of 400 s. -1 The shear rate measured at approximately 30 kP or less, in some embodiments approximately 20 kP or less, in some embodiments approximately 15 kP or less, and in some embodiments approximately 1 kP to approximately 10 kP.

[0025] Despite exhibiting good flow properties, the polymer composition retains high impact and tensile strength, which provides enhanced flexibility to the resulting parts. For example, the polymer composition can exhibit approximately 4 kJ / m² as measured at 23°C according to ISO 179-1:2010. 2 Or a greater notched impact strength for simply supported beams, for example, about 5 kJ / m in some embodiments. 2 Approximately 20 kJ / m 2 And in some implementations, approximately 8 kJ / m 2 Approximately 15 kJ / m 2The polymer composition may also exhibit: a tensile stress at break of about 100 MPa or greater, in some embodiments about 130 MPa to about 350 MPa, and in some embodiments about 160 MPa to about 300 MPa; a tensile strain at break of about 1% or greater, in some embodiments about 1.5% to about 5%; and / or a tensile modulus of about 8,000 MPa or greater, in some embodiments about 10,000 MPa to about 25,000 MPa, and in some embodiments about 15,000 MPa to about 20,000 MPa. Tensile properties can be determined according to ISO 527:2019 at a temperature of 23°C. The composition may also exhibit a flexural strength of about 100 MPa or greater, in some embodiments about 150 MPa to about 400 MPa, and in some embodiments about 200 MPa to about 350 MPa; a flexural fracture strain of about 1% or greater, in some embodiments about 1.5% to about 5%; and / or a flexural modulus of 8,000 MPa or greater, in some embodiments about 10,000 MPa to about 25,000 MPa, and in some embodiments about 15,000 MPa to about 20,000 MPa. Flexural properties can be determined at 23°C according to ISO 178:2019.

[0026] The polymer composition also exhibits good insulating properties. The insulating properties of the polymer composition can be characterized by a high comparative tracking index (“CTI”), for example, about 150 volts or higher as measured according to IEC 60112:2003, about 160 volts or higher in some embodiments, about 170 volts or higher in some embodiments, about 200 volts or higher in some embodiments, and about 250 volts to about 500 volts in some embodiments. This insulating property can be achieved at relatively small thickness values ​​as described above.

[0027] Various embodiments of the present invention will now be described in more detail.

[0028] I. polymer composition

[0029] A. polymer matrix

[0030] The polymer matrix typically comprises about 10 wt.% to about 70 wt.% of the polymer composition, about 20 wt.% to about 60 wt.% in some embodiments, about 25 wt.% to about 55 wt.% in some embodiments, and about 30 wt.% to about 50 wt.% in some embodiments. The polymer matrix contains at least one polyarylene sulfide. For example, the polyarylene sulfide typically comprises about 50 wt.% to 100 wt.% of the polymer matrix, about 70 wt.% to 100 wt.% in some embodiments, and about 90 wt.% to 100 wt.% (e.g., 100 wt.%) in some embodiments.

[0031] Polyaryl sulfides can be homopolymers or copolymers. For example, selective combinations of dihaloaromatic compounds can yield polyaryl sulfide copolymers containing not less than two different units. For instance, when p-dichlorobenzene is used in combination with m-dichlorobenzene or 4,4'-dichlorodiphenyl sulfone, a polyaryl sulfide copolymer can be formed, which comprises segments having the following structure:

[0032]

[0033] and chain segments with the following structure:

[0034]

[0035] Or a chain segment with the following structure:

[0036] .

[0037] Polyaryl sulfides can be linear, semi-linear, branched, or cross-linked. Linear polyaryl sulfides typically contain 80 mol% or more of repeating units –(Ar–S)–. Such linear polymers may also contain small amounts of branched or cross-linked units, but the amount of branched or cross-linked units is typically less than about 1 mol% of the total monomer units of the polyaryl sulfide. Linear polyaryl sulfide polymers can be random copolymers or block copolymers containing the aforementioned repeating units. Semi-linear polyaryl sulfides can also have cross-linked or branched structures, which are introduced into the polymer in small amounts by one or more monomers having three or more reactive functional groups. For example, the monomeric component used to form a semi-linear polyaryl sulfide may include a certain amount of a polyhalogenated aromatic compound having two or more halogen substituents per molecule, which can be used to prepare branched polymers. Such monomers can be derived from the formula R'X. nThe expression indicates that X is selected from chlorine, bromine and iodine respectively, n is an integer from 3 to 6, and R' is an n-valent polyvalent aromatic free radical that may have up to about 4 methyl substituents, and the total number of carbon atoms in R' is in the range of 6 to about 16. Examples of polyhalogenated aromatic compounds with more than two halogen substitutions per molecule that can be used to form semi-linear polyaryl sulfides include 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, 1,3-dichloro-5-bromobenzene, 1,2,4-triiodobenzene, 1,2,3,5-tetrabromobenzene, hexachlorobenzene, 1,3,5-trichloro-2,4,6-trimethylbenzene, 2,2',4,4'-tetrachlorobiphenyl, 2,2',5,5'-tetraiodobiphenyl, 2,2',6,6'-tetrabromo-3,3',5,5'-tetramethylbiphenyl, 1,2,3,4-tetrachloronaphthalene, 1,2,4-tribromo-6-methylnaphthalene, and mixtures thereof.

[0038] If desired, polyarylene sulfides can be functionalized. For example, disulfide compounds containing reactive functional groups (e.g., carboxyl, hydroxyl, amine, etc.) can react with polyarylene sulfides. Functionalization of polyarylene sulfides can further provide binding sites between any impact modifier and the polyarylene sulfide, which can improve the distribution of the impact modifier throughout the polyarylene sulfide and prevent phase separation. The disulfide compound can undergo a chain-splitting reaction with the polyarylene sulfide during melt processing to reduce its overall melt viscosity. When used, the disulfide compound typically constitutes about 0.01 wt.% to about 3 wt.% of the polymer composition, about 0.02 wt.% to about 1 wt.% in some embodiments, and about 0.05 wt.% to about 0.5 wt.% in some embodiments. The ratio of the amount of polyarylene sulfide to the amount of disulfide compound can also be about 1000:1 to about 10:1, about 500:1 to about 20:1, or about 400:1 to about 30:1. Suitable disulfide compounds are generally those having the following formula:

[0039] R 3 –S–S–R 4

[0040] Where R 3 and R 4 They can be the same or different and independently comprise hydrocarbon groups of 1 to 20 carbons. For example, R 3 and R 4 It can be an alkyl, cycloalkyl, aryl, or heterocyclic group. In some embodiments, R 3 and R 4 These are typically non-reactive functional groups, such as phenyl, naphthyl, ethyl, methyl, propyl, etc. Examples of such compounds include diphenyl disulfide, naphthyl disulfide, dimethyl disulfide, diethyl disulfide, and dipropyl disulfide. 3 and R 4Reactive functional groups can also be included at the ends of disulfide compounds. For example, R 3 and R 4 At least one of them may include a terminal carboxyl group, a hydroxyl group, a substituted or unsubstituted amino group, a nitro group, etc. Examples of compounds may include, but are not limited to, 2,2'-diaminodiphenyl disulfide, 3,3'-diaminodiphenyl disulfide, 4,4'-diaminodiphenyl disulfide, dibenzyl disulfide, dithiosalicylic acid (or 2,2'-dithiobenzoic acid), dithioglycolic acid, α,α'-dithiodilactate, β,β'-dithiodilactate, 3,3'-dithiodipyridine, 4,4'-dithiomorpholine, 2,2'-dithiobis(benzothiazole), 2,2'-dithiobis(benzimidazole), 2,2'-dithiobis(benzoxazole), 2-(4'-morpholinodithio)benzothiazole, etc., and mixtures thereof.

[0041] As described above, the polymer matrix can exhibit a melt flow index greater than about 550 g / 10 min, as determined according to ASTM D1238-13 at a load of 2.16 kg and a temperature of 190°C, greater than about 600 g / 10 min in some embodiments, about 650 g / 10 min to about 1,000 g / 10 min in some embodiments, and about 700 g / 10 min to about 900 g / 10 min in some embodiments. This target melt flow index can be achieved by using a single polyarylene sulfide or by using a blend of polyarylene sulfides with different melt flow indices. In one embodiment, for example, the polymer matrix can employ a first polyarylene sulfide having a first melt flow index and a second polyarylene sulfide having a second melt flow index. The ratio of the first melt flow index to the second melt flow index can be, for example, about 1.5 to about 3, about 1.6 to about 2.8 in some embodiments, and about 1.8 to about 2.4 in some embodiments. The first melt flow index can be, for example, from about 700 to about 2000 g / 10 min, in some embodiments from about 750 to about 1500 g / 10 min, and in some embodiments from about 800 to about 1200 g / 10 min. Similarly, the second melt flow index can be from about 250 to about 700 g / 10 min, in some embodiments from about 300 to about 650 g / 10 min, and in some embodiments from about 400 to about 600 g / 10 min. Depending on the exact melt flow index selected, the relative weight percentage of each polymer can thus be selectively controlled to achieve the target melt flow index of the polymer matrix. For example, typically, the first polyarylene sulfide and the second polyarylene sulfide each account for about 30 wt.% to about 70 wt.% of the polymer matrix, in some embodiments from about 35 wt.% to about 65 wt.%, and in some embodiments from about 40 wt.% to about 60 wt.%.

[0042] Polyarylene sulfides, as described above, typically have a DTUL value of about 70°C to about 220°C, determined according to ISO 75-2:2013 under a load of 1.8 MPa, in some embodiments about 90°C to about 200°C, and in some embodiments about 120°C to about 180°C. Polyarylene sulfides also typically have a glass transition temperature of about 50°C to about 120°C, in some embodiments about 60°C to about 115°C, and in some embodiments about 70°C to about 110°C, and a melting temperature of about 220°C to about 340°C, in some embodiments about 240°C to about 320°C, and in some embodiments about 260°C to about 300°C.

[0043] B. Impact modifier

[0044] As described above, the polymer composition may also contain an impact modifier. Such an impact modifier typically comprises about 1 to about 30 parts by weight per 100 parts by weight of the polymer matrix, about 2 to about 20 parts by weight in some embodiments, and about 5 to about 15 parts by weight in some embodiments. For example, the impact modifier may comprise about 0.1 wt.% to about 20 wt.% of the polymer composition, about 0.5 wt.% to about 15 wt.% in some embodiments, and about 1 wt.% to about 10 wt.% in some embodiments.

[0045] Examples of suitable impact modifiers may include, for example, polyepoxides, polyurethanes, polybutadiene, acrylonitrile-butadiene-styrene, polyamides, block copolymers (e.g., polyether-polyamide block copolymers), and mixtures thereof. In one embodiment, “epoxy-functionalized” olefin copolymers are used because they contain an average of two or more epoxy functional groups per molecule. The copolymer typically comprises olefin monomer units derived from one or more α-olefins. Examples of such monomers include, for example, straight-chain and / or branched α-olefins having 2 to 20 carbon atoms and typically 2 to 8 carbon atoms. Specific examples include: ethylene, propylene, 1-butene; 3-methyl-1-butene; 3,3-dimethyl-1-butene; 1-pentene; 1-pentene having one or more methyl, ethyl, or propyl substituents; 1-hexene having one or more methyl, ethyl, or propyl substituents; 1-heptene having one or more methyl, ethyl, or propyl substituents; 1-octene having one or more methyl, ethyl, or propyl substituents; 1-nonene having one or more methyl, ethyl, or propyl substituents; 1-decene substituted with ethyl, methyl, or dimethyl; 1-dodecene; and styrene. Particularly desirable α-olefin monomers are ethylene and propylene. Copolymers may also contain epoxy-functionalized monomer units. An example of such a unit is an epoxy-functionalized (meth)acrylic acid monomer component. As used herein, the term "(meth)acrylic acid" includes acrylic acid and methacrylic acid monomers, as well as their salts or esters, such as acrylate and methacrylate monomers. For example, suitable epoxy-functionalized (meth)acrylate monomers may include, but are not limited to, those containing 1,2-epoxy groups, such as glycidyl acrylate and glycidyl methacrylate. Other suitable epoxy-functionalized monomers include allyl glycidyl ether, ethyl glycidyl acrylate, and itaconic acid glycidyl ester. Other suitable monomers may also be used to help achieve the desired molecular weight.

[0046] Of course, the copolymer may also contain other monomer units known in the art. For example, another suitable monomer may include a non-epoxy-functionalized (meth)acrylic acid monomer. Examples of such (meth)acrylic monomers may include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, sec-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, isoamyl acrylate, isobornyl acrylate, n-hexyl acrylate, 2-ethylbutyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, n-decyl acrylate, methylcyclohexyl acrylate, cyclopentyl acrylate, cyclohexyl acrylate, methyl methacrylate, ethyl methacrylate, 2-hydroxyethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, isopropyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, n-hexyl methacrylate, isoamyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, 2-ethylbutyl methacrylate, methylcyclohexyl methacrylate, cinnamon methacrylate, crotonyl methacrylate, cyclohexyl methacrylate, cyclopentyl methacrylate, 2-ethoxyethyl methacrylate, isobornyl methacrylate, etc., and combinations thereof. For example, in one particular embodiment, the copolymer can be a terpolymer formed from an epoxy-functionalized (meth)acrylic acid monomer component, an α-olefin monomer component, and a non-epoxy-functionalized (meth)acrylic acid monomer component. The copolymer can be, for example, a poly(ethylene-co-butyl acrylate-co-glycidyl methacrylate) having the following structure:

[0047]

[0048] Where x, y, and z are 1 or greater.

[0049] The appropriate portion of the monomer components can be selected to achieve a balance between epoxy reactivity and melt flow rate. More specifically, a high epoxy monomer content can result in good reactivity with polyarylates, but too high a content may reduce the melt flow rate to the extent that the copolymer adversely affects the melt strength of the polymer blend. Therefore, in most embodiments, the epoxy-functionalized (meth)acrylate monomer comprises about 1 wt.% to about 20 wt.% of the copolymer, in some embodiments about 2 wt.% to about 15 wt.%, and in some embodiments about 3 wt.% to about 10 wt.%. Similarly, the α-olefin monomer can comprise about 55 wt.% to about 95 wt.% of the copolymer, in some embodiments about 60 wt.% to about 90 wt.%, and in some embodiments about 65 wt.% to about 85 wt.%. When used, other monomer components (e.g., non-epoxy-functionalized (meth)acrylate monomers) can comprise about 5 wt.% to about 35 wt.% of the copolymer, in some embodiments about 8 wt.% to about 30 wt.%, and in some embodiments about 10 wt.% to about 25 wt.%. According to ASTM D1238-13, at a load of 2.16 kg and a temperature of 190 °C, the resulting melt flow rate is typically from about 1 g / 10 min to about 30 g / 10 min (“g / 10 min”), in some embodiments from about 2 g / 10 min to about 20 g / 10 min, and in some embodiments from about 3 g / 10 min to about 15 g / 10 min.

[0050] If desired, other impact modifiers can be used in combination with epoxy-functionalized impact modifiers. For example, other impact modifiers may include block copolymers in which at least one phase is made of a material that is hard at room temperature but fluid when heated, while the other phase is a softer material that is rubbery at room temperature. For example, the block copolymer may have an AB or ABA block copolymer repeating structure, where A represents a hard segment and B is a soft segment. Non-limiting examples of impact modifiers having an AB repeating structure include polyamide / polyether, polysulfone / polydimethylsiloxane, polyurethane / polyester, polyurethane / polyether, polyester / polyether, polycarbonate / polydimethylsiloxane, and polycarbonate / polyether. Triblock copolymers may also contain polystyrene as a hard segment and polybutadiene, polyisoprene, or polyethylene-co-polybutene as soft segments. Similarly, styrene-butadiene repeating copolymers and polystyrene / polyisoprene repeating polymers can be used. In one particular embodiment, the block copolymer may have alternating polyamide and polyether blocks. These materials are commercially available, for example, from Atofina under the trade name PEBAX™. Polyamide blocks can be derived from copolymers of diacid and diamine components, or prepared by homopolymerization of cyclic lactams. Polyether blocks can be derived from homopolymers or copolymers of cyclic ethers such as ethylene oxide, propylene oxide, and tetrahydrofuran.

[0051] C. Mineral particles

[0052] As noted, mineral particles are also used in the polymer composition. These particles are typically present in amounts of about 10 to about 50 parts by weight per 100 parts by weight of the polymer matrix, in some embodiments about 15 to about 45 parts by weight, and in some embodiments about 20 to about 40 parts by weight. Various types of mineral particles can be used, as is known in the art. For example, clay minerals are particularly suitable for this invention. Examples of such clay minerals include, for example, talc, halloysite, kaolinite, illite, montmorillonite, vermiculite, palygorskite, pyrophyllite, etc., and combinations thereof. Instead of clay minerals, or in addition to clay minerals, other mineral particles may be used, such as metal silicate particles (e.g., calcium silicate, aluminum silicate, mica, diatomite, wollastonite, etc.); alkaline earth metal carbonate particles; and so on. When used, alkaline earth metal carbonate particles may be selected from, for example, calcium carbonate, magnesium carbonate, calcium magnesium carbonate, barium carbonate, etc. Such carbonates may be derived from natural sources, such as marble, chalk, limestone, dolomite, etc. Regardless of the specific material, mineral particles typically have a median particle size of about 0.5 micrometers to about 10 micrometers, in some embodiments about 0.6 micrometers to about 8 micrometers, and in some embodiments about 1 micrometer to about 5 micrometers, determined, for example, using sedimentation maps (e.g., a SediGraph III 5120 from Micromeritics) and / or using laser diffraction techniques (e.g., using a Horiba LA-960 particle size analyzer) according to ISO 13320:2020. In some embodiments, the particles may also have a generally spherical shape because their aspect ratio (e.g., average length or diameter divided by average thickness) is close to 1, for example about 0.6 to about 2.0, in some embodiments about 0.7 to about 1.5, and in some embodiments about 0.8 to about 1.2.

[0053] The mineral particles may have a relatively low moisture content, for example, about 0.5 wt.% or less, about 0.3 wt.% or less in some embodiments, and about 0.2 wt.% or less in some embodiments. The “moisture content” can be determined by measuring the weight loss after drying the particles to constant weight in an oven at 110°C (i.e., drying to dryness at 110°C).

[0054] Although not essential, the particles may also contain surface treatment agents to aid in dispersion and compatibility with the polymer matrix. Suitable surface treatment agents may include, for example, aliphatic carboxylic acids (e.g., stearic acid, palmitic acid, lignite acid, decanoic acid, lauric acid, myristic acid, isostearic acid, waxy acid), and mixtures thereof, having 10 to 24 carbon atoms in their chains. When used, the surface treatment agent may be chemisorbed onto the particles to promote dispersion in the polymer matrix. For example, fatty acids (e.g., stearic acid) may react with alkaline earth metal carbonates (e.g., calcium carbonate) to form a chemisorbed coating (e.g., calcium stearate) thereon. To maintain a low moisture content, the surface treatment may be carried out in a dry atmosphere containing the surface treatment agent as a liquid (e.g., as droplets) in an indirectly heated container, such as by means of a heated jacket containing, for example, a heated fluid, such as heated oil. The temperature of the atmosphere in the container may be varied and controlled so that the selected atmosphere reaction temperature can be selected and monitored. The container may include an elongated heated cylindrical structure. Ideally, the target temperature is maintained throughout the area where the surface treatment agent is applied and away from that area, for example, from about 80°C to about 300°C, and in some embodiments from about 100°C to about 200°C. The resulting surface-treated particles may have a moisture content within the above range, or they may be further dried to achieve the desired moisture content.

[0055] D. Reinforcing Fibers

[0056] Reinforcing fibers can also be used in some embodiments of the invention. Any type of reinforcing fiber from a variety of different types can generally be used, such as polymer fibers, metal fibers, carbon fibers (e.g., graphite, carbides, etc.), inorganic fibers, and combinations thereof. Inorganic fibers are particularly suitable, for example, those derived from glass; titanates (e.g., potassium titanate); silicates, such as neosilicates, tansilicates, chain silicates (e.g., calcium chain silicates, such as wollastonite; calcium magnesium chain silicates, such as tremolite; calcium magnesium iron chain silicates, such as actinolite; magnesium iron chain silicates, such as anthocyanin; etc.), folin silicates (e.g., aluminum folin silicates, such as palygorskite), reticulate silicates, etc.; sulfates, such as calcium sulfate (e.g., dehydrated or anhydrous gypsum); mineral wool (e.g., rock wool or slag wool); etc. Glass fibers are particularly suitable, for example, those formed from E-glass, A-glass, C-glass, D-glass, AR-glass, R-glass, S1-glass, S2-glass, and mixtures thereof. If desired, a sizing agent or other coating known in the art may be provided for the reinforcing fibers. Regardless of the specific type chosen, it is generally desirable for the fibers to have a relatively low modulus of elasticity to enhance the processability of the resulting polymer composition. For example, the fibers may have a Young's modulus of elasticity of less than about 76 GPa as determined according to ASTM C1557-14, less than about 75 GPa in some embodiments, and from about 10 GPa to about 74 GPa in some embodiments.

[0057] If desired, at least a portion of the reinforcing fibers may have relatively flat cross-sectional dimensions, i.e., aspect ratios of about 1.5 to about 10, about 2 to about 8 in some embodiments, and about 3 to about 5 in some embodiments. This aspect ratio is determined by dividing the cross-sectional width of the fiber (i.e., along the long axis) by the cross-sectional thickness of the fiber (i.e., along the short axis). Such fibers may be elliptical, rectangular, rectangular with one or more rounded corners, etc. The cross-sectional width of the fiber may be about 1 micrometer to about 50 micrometers, about 5 micrometers to about 45 micrometers in some embodiments, and about 10 micrometers to about 35 micrometers in some embodiments. The fiber may also have a thickness of about 0.5 micrometers to about 30 micrometers, about 1 micrometer to about 20 micrometers in some embodiments, and about 3 micrometers to about 15 micrometers in some embodiments. It should be understood that the cross-sectional thickness and / or width need not be uniform across the entire cross-section. In such cases, the cross-sectional width is considered as the maximum dimension along the long axis of the fiber, and the cross-sectional thickness is considered as the maximum dimension along the short axis. For example, the cross-sectional thickness of an elliptical fiber is the minor axis of the ellipse.

[0058] The reinforcing fibers may also have a narrow size distribution. That is, at least about 60 vol.% of the fibers, in some embodiments at least about 70 vol.% of the fibers, and in some embodiments at least about 80 vol.% of the fibers may have a width and / or thickness within the above range. The fibers may be continuous fibers or chopped fibers, for example, those with a length of about 1 mm to about 15 mm, and in some embodiments about 2 mm to about 6 mm. The dimensions of the fibers (e.g., length, width, and thickness) can be determined using known optical microscopy techniques.

[0059] When used, the amount of reinforcing fibers can be selectively controlled to achieve a desired combination of properties. For example, the reinforcing fibers can be used in amounts of about 50 to about 150 parts by weight per 100 parts by weight of the polymer matrix, in some embodiments about 60 to about 125 parts by weight, and in some embodiments about 70 to about 120 parts by weight. For example, the reinforcing fibers can comprise about 10 wt.% to about 60 wt.% of the polymer composition, in some embodiments about 20 wt.% to about 50 wt.%, and in some embodiments about 25 wt.% to about 45 wt.%. The relative ratio of the reinforcing fibers to the mineral particles can also be selectively controlled. For example, the weight ratio of the reinforcing fibers to such particles can be about 2 or greater, in some embodiments about 2.5 to about 8, and in some embodiments about 3 to about 6.

[0060] E. Optional components

[0061] In addition to the components described above, the polymer composition may also contain a variety of other optional components to help improve its overall properties. For example, in one embodiment, a siloxane polymer may be used in the polymer composition. This siloxane polymer typically comprises about 0.1 parts by weight to about 10 parts by weight per 100 parts by weight of the polymer matrix, about 0.2 parts by weight to about 5 parts by weight in some embodiments, and about 0.5 parts by weight to about 4 parts by weight in some embodiments. For example, the siloxane polymer may comprise about 0.05 wt.% to about 5 wt.% of the polymer composition, about 0.1 wt.% to about 4 wt.% in some embodiments, and about 0.5 wt.% to about 2 wt.% in some embodiments. The siloxane polymer typically has a high molecular weight, such as about 100,000 g / mol or greater, about 200,000 g / mol or greater in some embodiments, and about 500,000 g / mol to about 2,000,000 g / mol in some embodiments. Siloxane polymers may also have relatively high kinematic viscosity at 25°C, for example, about 10,000 centipoise or higher, about 30,000 centipoise or higher in some embodiments, and about 50,000 centipoise to about 50 × 10⁻⁶ centipoise in some embodiments. 6 centiliter, for example, about 1 × 10 6 centiliter to 50×10 6 Centiliter. The viscosity of siloxane polymers can be determined according to ASTM D445-21.

[0062] Any variety of high molecular weight siloxane polymers can generally be used in polymer compositions. High molecular weight siloxane polymers typically comprise repeating units of siloxane monomer residues. As used herein, "siloxane" refers to a repeating unit of monomer residues having the following structure:

[0063]

[0064] Where R 1 and R 2 Independently, it is either a hydrogen or hydrocarbon group, referred to as the "M" group in silicone chemistry.

[0065] Silicone resins may include branch points, for example

[0066]

[0067] In silicone chemistry, it is referred to as the "Q" group, or

[0068]

[0069] In silicone chemistry, it is referred to as the "T" group.

[0070] As used herein, the term "alkyl group" refers to a monovalent group (e.g., alkyl, such as ethyl, or aryl, such as phenyl) formed by removing hydrogen atoms from a hydrocarbon. In one or more embodiments, the siloxane monomer residue can be any dialkylsiloxane, diarylsiloxane, dialkylarylsiloxane, or diarylalkylsiloxane having the same or different alkyl, aryl, alkylaryl, or aralkyl moiety. In one embodiment, R 1 and R 2 Each independently is C1 to C 20 C1 to C 12 Or C1 to C6 alkyl (e.g., methyl, ethyl, propyl, butyl, etc.), aryl (e.g., phenyl), alkylaryl, aralkyl, cycloalkyl (e.g., cyclopentyl), arylenyl, alkenyl, cycloalkenyl (e.g., cyclohexenyl), alkoxy (e.g., methoxy), etc., and combinations thereof. In various embodiments, R 1 and R 2 They can have the same or different numbers of carbon atoms. In various embodiments, R 1 and R 2 Each hydrocarbon group is a saturated and optionally straight-chain alkyl group. Furthermore, in this embodiment, the alkyl group corresponds to the R group of the polymer chain. 1 and R 2 Each of them can be the same. (Applicable to R) 1 and R 2 Non-limiting examples of alkyl groups include methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, isobutyl, tert-butyl, or combinations of two or more of these.

[0071] In addition, siloxane polymers can contain various end groups as R 1 and / or R 2 Groups, such as vinyl, hydroxyl, hydride, isocyanate, epoxy, acidic, halogen, alkoxy, acyloxy, ketoxime, amino, amide, acid amide, aminooxy, mercapto, alkenyloxy, alkoxyalkoxy, or aminooxy, and combinations thereof. Furthermore, the polymer composition may include a mixture of two or more siloxane polymers.

[0072] In some embodiments, high molecular weight siloxane polymers can be improved by copolymerizing a variety of siloxane polymers having low weight-average molecular weights (e.g., less than 100,000 g / mol) with polysiloxane linkers. For example, in a particular embodiment, a resin can be formed by copolymerizing one or more low molecular weight siloxane polymers with linear polydiorganosiloxane linkers, as described in U.S. Patent No. 6,072,012 to Juen et al. The substantially linear polydiorganosiloxane linkers can have the following general formula:

[0073] (R 3(3-p) R 4 p SiO 1 / 2 (R) 3 2SiO 2 / 2 ) x ((R 3 R 4 SiO 2 / 2 (R) 3 2SiO 2 / 2 ) x ) y (R 3 (3-p) R 4 p SiO 1 / 2 )

[0074] in,

[0075] Each R 3 It is a monovalent group independently selected from alkyl, aryl, and aralkyl groups;

[0076] Each R 4 It is a monovalent group independently selected from hydrogen, hydroxyl, alkoxy, oxime, alkyl oxime, and aryl oxime, wherein at least two of them are R. 5 Groups are typically present in each molecule and are bonded to different silicon atoms;

[0077] p is 0, 1, 2, or 3;

[0078] x is 0 to 200, and in some implementations is 0 to 100; and

[0079] y is 0 to 200, and in some implementations it is 0 to 100.

[0080] In some embodiments, the siloxane polymer may be provided in the form of a masterbatch comprising a carrier resin. For example, the carrier resin may comprise about 0.05 wt.% to about 15 wt.% of the polymer composition, about 0.1 wt.% to about 10 wt.% in some embodiments, and about 0.5 wt.% to about 8 wt.% in some embodiments. Any carrier resin of various types can be used, such as polyolefins (ethylene polymers, propylene polymers, etc.), polyamides, etc. For example, in one embodiment, the carrier resin is an ethylene polymer. The ethylene polymer may be ethylene and α-olefins (e.g., C3-C...). 20 α-olefins or C3-C 12Copolymers of α-olefins. Suitable α-olefins can be linear or branched (e.g., one or more C1-C3 alkyl branches, or aryl). Specific examples include: 1-butene; 3-methyl-1-butene; 3,3-dimethyl-1-butene; 1-pentene; 1-pentene having one or more methyl, ethyl, or propyl substituents; 1-hexene having one or more methyl, ethyl, or propyl substituents; 1-heptene having one or more methyl, ethyl, or propyl substituents; 1-octene having one or more methyl, ethyl, or propyl substituents; 1-nonene having one or more methyl, ethyl, or propyl substituents; 1-decene substituted with ethyl, methyl, or dimethyl; 1-dodecene; and styrene. Particularly desirable α-olefin comonomers are 1-butene, 1-hexene, and 1-octene. The ethylene content of this copolymer can be from about 60 mol.% to about 99 mol.%, in some embodiments from about 80 mol.% to about 98.5 mol.%, and in some embodiments from about 87 mol.% to about 97.5 mol.%. The α-olefin content can also be from about 1 mol.% to about 40 mol.%, in some embodiments from about 1.5 mol.% to about 15 mol.%, and in some embodiments from about 2.5 mol.% to about 13 mol.%. The density of the ethylene polymer can vary depending on the type of polymer used, but is typically from about 0.85 g / cm³ to about 0.96 g / cm³. 3 For example, the density of polyethylene "plastic" can be approximately 0.85 g / cm³. 3 Approximately 0.91 g / cm³ 3 Similarly, the density of linear low-density polyethylene (LLDPE) can be approximately 0.91 g / cm³. 3 Approximately 0.940 g / cm³ 3 Low-density polyethylene (LDPE) has a density of approximately 0.910 g / cm³. 3 Approximately 0.940 g / cm³ 3 High-density polyethylene (HDPE) has a density of approximately 0.940 g / cm³. 3 Approximately 0.960 g / cm³ 3 For example, as determined according to ASTM D792. Some non-limiting examples of high molecular weight siloxane polymer masterbatches that can be used include those available from Dow Corning under the trade names MB50-001, MB50-002, MB50-313, MB50-314, and MB50-321.

[0081] If desired, an organosilane compound may be used in the polymer composition, for example, in amounts of about 0.1 parts by weight to about 8 parts by weight per 100 parts by weight of polyarylether, about 0.3 parts by weight to about 5 parts by weight in some embodiments, and about 0.5 parts by weight to about 3 parts by weight in some embodiments. For example, the organosilane compound may comprise about 0.01 wt.% to about 3 wt.% of the polymer composition, about 0.05 wt.% to about 2 wt.% in some embodiments, and about 0.1 wt.% to about 1 wt.% in some embodiments. For example, the organosilane compound may be any alkoxysilane known in the art, such as vinylalkoxysilane, epoxyalkoxysilane, aminoalkoxysilane, mercaptoalkoxysilane, and combinations thereof. In one embodiment, for example, the organosilane compound may have the following general formula:

[0082] R 5 -Si-(R 6 )3,

[0083] in,

[0084] R 5 It includes sulfide groups (e.g., -SH), alkyl sulfides containing 1 to 10 carbon atoms (e.g., mercaptopropyl, mercaptoethyl, mercaptobutyl, etc.), alkenyl sulfides containing 2 to 10 carbon atoms, alkynyl sulfides containing 2 to 10 carbon atoms, amino groups (e.g., NH2), aminoalkyl groups containing 1 to 10 carbon atoms (e.g., aminomethyl, aminoethyl, aminopropyl, aminobutyl, etc.), aminoalkenyl groups containing 2 to 10 carbon atoms, and aminoalkynyl groups containing 2 to 10 carbon atoms, etc.

[0085] R 6 It is an alkoxy group with 1 to 10 carbon atoms, such as methoxy, ethoxy, propoxy, etc.

[0086] Representative examples of organosilane compounds that may be included in mixtures include mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane, aminopropyltriethoxysilane, aminoethyltriethoxysilane, aminopropyltrimethoxysilane, aminoethyltrimethoxysilane, ethylenetrimethoxysilane, ethylenetriethoxysilane, acetylenetrimethoxysilane, acetylenetriethoxysilane, aminoethylaminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropylmethyldimethoxysilane or 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyl Trimethoxysilanes, N-methyl-3-aminopropyltrimethoxysilanes, N-phenyl-3-aminopropyltrimethoxysilanes, bis(3-aminopropyl)tetramethoxysilanes, bis(3-aminopropyl)tetraethoxydisiloxanes, γ-aminopropyltrimethoxysilanes, γ-aminopropyltriethoxysilanes, γ-aminopropylmethyldimethoxysilanes, γ-aminopropylmethyldiethoxysilanes, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilanes, N-phenyl-γ-aminopropyltrimethoxysilanes, γ-diallylaminopropyltrimethoxysilanes, γ-diallylaminopropyltrimethoxysilanes, etc., and combinations thereof. Particularly suitable organosilane compounds are 3-aminopropyltriethoxysilanes and 3-mercaptopropyltrimethoxysilanes.

[0087] Other components that may be included in the composition may include, for example, metal hydroxide particles (e.g., alumina trihydrate), pigments (e.g., black pigments), antioxidants, stabilizers, crosslinking agents, surfactants, waxes, flow promoters, solid solvents, and other materials added to enhance performance and processability.

[0088] II. Melt processing

[0089] As is known in the art, the combination of polyarylene sulfides, impact modifiers, mineral particles, reinforcing fibers, and various other optional additives can vary. For example, materials can be fed simultaneously or sequentially into a melt processing apparatus for dispersing the blend. Batch and / or continuous melt processing techniques can be employed. For example, mixers / kneaders, Banbury mixers, Farrel continuous mixers, single-screw extruders, twin-screw extruders, roller mills, etc., can be used to blend and melt process materials. A particularly suitable melt processing apparatus is a co-rotating twin-screw extruder (e.g., a Leistritz co-rotating fully intermeshing twin-screw extruder). This extruder can include inlets and outlets and provides high-intensity distribution and dispersion mixing. For example, components can be fed into the same or different inlets of a twin-screw extruder and melt-blended to form a substantially homogeneous melt mixture. Melt blending can occur under high shear / pressure and heat to ensure adequate dispersion. For example, melt processing can be performed at temperatures ranging from about 100°C to about 500°C, and in some embodiments from about 150°C to about 300°C. Similarly, the apparent shear rate during melt processing can be about 100 seconds. -1 Approximately 10,000 seconds -1 And in some implementations, approximately 500 seconds. -1 Approximately 1500 seconds -1 Of course, other variables can also be controlled, such as the residence time during melt processing (which is inversely proportional to the throughput), to achieve the desired uniformity.

[0090] If desired, one or more distributing and / or dispersing mixing elements may be used within the mixing section of the melt processing unit. Suitable distributing mixers may include, for example, Saxon, Dulmage, Cavity Transfer mixers, etc. Similarly, suitable dispersing mixers may include Blister rings, Leroy / Maddock, CRD mixers, etc. It is known in the art that the aggressiveness of mixing can be further enhanced by using pins in the barrel that generate folding and reorientation of the polymer melt, such as those used in Buss kneader extruders, cavity transfer mixers, and Vortex Intermeshing Pin mixers. The screw speed can also be controlled to improve the properties of the composition. For example, the screw speed may be about 400 rpm or lower, in one embodiment, for example, about 200 rpm to about 350 rpm, or about 225 rpm to about 325 rpm. In one embodiment, compounding conditions may be balanced to provide polymer compositions exhibiting improved properties. For example, compounding conditions may include screw design to provide mild, moderate, or aggressive screw conditions. For example, the system can have a mildly aggressive screw design where the screw has a single melting section in the downstream half of the screw, designed for mild melting and homogenization of the distributed melt. A moderately aggressive screw design can have a stronger melting section upstream of the packing feed barrel, which focuses more on stronger dispersing elements for uniform melting. Additionally, it can have another mild mixing section downstream to mix the packing. While weaker, this section can still increase the screw's shear strength, making it stronger overall than the mildly aggressive design. A highly aggressive screw design can have the strongest shear strength of the three. The main melting section can consist of a long string of highly dispersed kneaded blocks. The downstream mixing section can utilize the mixing of dispersing and densely dispersing elements to achieve uniform dispersion of all types of packing. The shear strength of the highly aggressive screw design can be significantly higher than the other two designs. In one embodiment, the system can include a moderately to aggressive screw design with relatively mild screw speeds (e.g., about 200 rpm to about 300 rpm).

[0091] The crystallization temperature of the resulting polymer composition (before forming the molded part) can be about 250°C or lower, about 100°C to about 245°C in some embodiments, and about 150°C to about 240°C in some embodiments. The melting temperature of the polymer composition can also be about 140°C to about 380°C, about 200°C to about 360°C in some embodiments, about 250°C to about 320°C in some embodiments, and about 260°C to about 300°C in some embodiments. The melting temperature and crystallization temperature can be determined using differential scanning calorimetry according to ISO 11357-3:2018, as is known in the art.

[0092] III. Molded parts

[0093] A variety of different techniques can be used to form molded parts from polymer compositions. Suitable techniques may include, for example, injection molding, low-pressure injection molding, extrusion compression molding, gas injection molding, foam injection molding, low-pressure gas injection molding, low-pressure foam injection molding, gas extrusion compression molding, foam extrusion compression molding, extrusion molding, foam extrusion molding, compression molding, foam compression molding, gas compression molding, etc. For example, an injection molding system including a mold into which the polymer composition can be injected can be used. The time inside the syringe can be controlled and optimized so that the polymer matrix is ​​not pre-cured. When the cycle time is reached and the cylinder is full to discharge, the composition can be injected into the mold cavity using a piston. Compression molding systems can also be used. As with injection molding, the molding of the polymer composition into the desired article also occurs within the mold. Any known technique, such as picking up the composition with an automated robotic arm, can be used to place it into the compression mold. The temperature of the mold can be maintained at or above the solidification temperature of the polymer composition for the required period of time to allow solidification. The molded product can then be solidified by bringing it to a temperature below the melt temperature. The resulting product can be demolded. The cycle time of each molding process can be adjusted to suit the polymer composition, so as to achieve full bonding and improve the overall process productivity.

[0094] IV. Composite structure

[0095] As described above, the unique properties of the polymer composition make it easier to integrally mold with metal parts having drastically different coefficients of thermal expansion. Therefore, if desired, the polymer composition can be applied to composite structures comprising a metal part and a resin part including the polymer composition of the present invention, wherein the metal part and the resin part are integrally molded and in contact. This can be achieved using various techniques, such as embedding molding processes, in which the polymer composition is molded (e.g., injection molded) onto a portion or the entire surface of the metal part. The metal part can comprise any number of different metals, such as aluminum, stainless steel, magnesium, nickel, chromium, copper, titanium, and their alloys. Due to its unique properties, the polymer composition can adhere to the metal part by flowing within and / or around surface indentations or pores. To improve adhesion, the metal part can optionally be pretreated to increase the degree and surface area of ​​the surface indentations. This can be achieved using mechanical techniques (e.g., sandblasting, grinding, flaring, punching, molding, etc.) and / or chemical techniques (e.g., etching, anodizing, etc.). In addition to surface pretreatment, the metal part can also be preheated at a temperature close to but below the melting temperature of the polymer composition. This can be achieved using a variety of techniques, such as contact heating, radiant gas heating, infrared heating, convection or forced convection air heating, induction heating, microwave heating, or combinations thereof. In any case, the polymer composition is typically injected into a mold containing optionally preheated metal parts.

[0096] V. electric vehicles

[0097] As previously mentioned, polymer compositions, molded parts, and / or composite structures are particularly suitable for components of electric vehicles. (See reference...) Figure 1 For example, one embodiment of an electric vehicle 112 including a powertrain 110 is shown. The powertrain 110 includes one or more motors 114 connected to a drivetrain 116, which in turn is mechanically connected to a drive shaft 120 and drive wheels 122. While not strictly necessary, the drivetrain 116 in this particular embodiment is also connected to an engine 118, although the description herein is equally applicable to purely electric vehicles. The motors 114 may be able to operate as motors or generators to provide propulsion and deceleration capabilities. The powertrain 110 also includes a propulsion source, such as a battery assembly 124 that stores and provides energy for use by the motors 114. The battery assembly 124 typically provides a high-voltage current output (e.g., DC current with a voltage of about 400 volts to about 800 volts) from one or more battery cell arrays that may include one or more battery cells.

[0098] The powertrain 110 may also include at least one power electronics module 126, which is connected to the battery assembly 124 (also commonly referred to as a battery pack) and may include power converters (e.g., converters, etc., and combinations thereof). The power electronics module 126 is typically connected to the motor 114 and provides the ability to transfer electrical energy bidirectionally between the battery assembly 124 and the motor 114. For example, the battery assembly 124 may provide DC voltage, while the motor 114 may require three-phase AC voltage to operate. The power electronics module 126 can convert the DC voltage to the three-phase AC voltage required by the motor 114. In regenerative mode, the power electronics module 126 can convert the three-phase AC voltage from the motor 114, which acts as a generator, to the DC voltage required by the battery assembly 124. The battery assembly 124 may also provide energy to other vehicle electrical systems. For example, the powertrain may use a DC / DC converter module 128 that converts the high-voltage DC output from the battery assembly 124 into a low-voltage DC power supply compatible with other vehicle loads, such as compressors and electric heaters. In a typical vehicle, the low-voltage system is electrically connected to the auxiliary battery 130 (e.g., a 12V battery). A battery energy control module (BECM) 133 may also be present, communicating with the battery assembly 124. The BECM 133 acts as a controller for the battery assembly 124 and may include an electronic monitoring system that manages the temperature and state of charge of each battery cell. The battery assembly 124 may also have a temperature sensor 131, such as a thermistor or other thermometer. The temperature sensor 131 may communicate with the BECM 133 to provide temperature data about the battery assembly 124. The temperature sensor 131 may also be located on or near the battery cells within the traction battery 124. It is also contemplated that more than one temperature sensor 131 may be used to monitor the temperature of the battery cells.

[0099] In some implementations, battery assembly 124 can be recharged via an external power source 136 (e.g., a power outlet). The external power source 136 can be electrically connected to an Electric Vehicle Supply Equipment (EVSE), which regulates and manages the power transfer between power source 136 and vehicle 112. EVSE 138 may have a charging connector 140 for insertion into a charging port 134 of vehicle 112. The charging port 134 can be any type of port configured to transfer power from EVSE 138 to vehicle 112 and can be electrically connected to a charger or on-board power conversion module 132. Power conversion module 132 can regulate the power supplied by EVSE 138 to provide appropriate voltage and current levels to battery assembly 124. Power conversion module 132 can interact with EVSE 138 to coordinate the delivery of power to vehicle 112.

[0100] The polymer compositions described herein may include, for example, Figure 1Among the various components of the electric vehicle shown. For example, the busbar (one example of which is...) Figure 2 (As shown) can be used to electrically connect each unit of battery assembly 124. See reference... Figure 3 For example, battery assembly 124 may include a plurality of battery cells 158. Battery cells 158 may be stacked side-by-side to form a battery cell group, sometimes referred to as a battery array. In one embodiment, battery cells 158 are prismatic lithium-ion batteries. However, battery cells having other geometries (cylindrical, pouch, etc.) and / or chemical compositions (nickel hydride, lead-acid, etc.) may alternatively be used within the scope of this disclosure. Each battery cell 158 includes a positive terminal (indicated by the symbol (+)) and a negative terminal (indicated by the symbol (-)). Battery cells 158 are arranged such that the terminals of each battery cell 158 are positioned adjacent to the terminals of adjacent battery cells 158 having opposite polarities. As used herein, the terms “battery,” “single cell,” and “battery cell” are used interchangeably to refer to any type of individual battery element used in a battery system. The batteries described herein generally include lithium-based batteries, but can also include various chemistry compositions and configurations, including iron phosphate, metal oxide, lithium-ion polymer, nickel metal hydride, nickel-cadmium, nickel-based batteries (hydrogen, zinc, cadmium, etc.), and any other battery type compatible with electric vehicles. For example, some implementations may use batteries from Panasonic. ® The 6831 NCR 18650 battery cell, or certain variations of the 18650 shape factor of 6.5cm × 1.8cm and approximately 45g.

[0101] As is known in the art, the bus is connected to the battery assembly 124 (e.g. Figure 3 The arrangement of each battery cell (as shown) can vary. (Refer to...) Figure 2 This illustration shows one embodiment of a busbar 10 including a conductor 12. The conductor 12 comprises a conductive material 18, such as copper, aluminum, aluminum alloy, etc., and is typically in the form of a solid rod, hollow tube, etc. The busbar 10 includes a connector portion 14 at either end, configured to mate with corresponding terminals of two or more batteries. An insulating portion 16 comprising a polymer composition as described herein (e.g., a coating material or molding material) may cover a portion of the conductive material of the conductor 12. To form the busbar 10, the insulating portion 16 may be applied to the surface of the conductive material 18. For example, a rod or tube of the conductive material 18 may be inserted into a pre-formed tube of the insulating coating 16, such as an extruded tube of a specific size and cut to the correct proportions, and the busbar 10 may then be formed into any suitable form. In another embodiment, the insulating coating may be applied to the surface of the conductive material 18 in a melt, and may be cured on the surface of the conductive material in the area of ​​application.

[0102] Of course, busbars of any suitable shape and size can be provided. For example, busbars can be used as templates for placing individual battery cells so that the battery cells are uniform in each prepared battery assembly. In such an embodiment, the busbars can hold the individual cells of the battery assembly 124 in place during the manufacturing process, and can be used to add thermal pads or injection housings that can be formed from the polymer compositions described herein without causing the individual battery cells to be misaligned.

[0103] Besides the busbar, other components can also use the polymer composition of the present invention. For example, Figure 4 A block diagram of the battery electronics of an electric vehicle 112 is shown. The battery electronics system shown includes a battery assembly 124 and a current sensor 142. As shown, the current sensor 142 is connected between the battery assembly 124 and a load / source 144. When the load / source 144 is a load such as one or more motors 114, the current sensor 142 can be configured to measure the current flowing from the battery assembly 124 to the load / source 144. Similarly, when the load / source 144 is a source such as an external power source 136, the current sensor 142 can be configured to measure the current flowing from the load / source 144 to the battery assembly 124. A battery electronic control module (BECM) 133 can be configured to power the current sensor 142 to operate it. The BECM 133 can also be configured to read the output generated by the current sensor 142, which indicates the current flowing between the battery assembly 124 and the load / source 144.

[0104] Figure 5 One embodiment of a current sensor 142 is shown. The current sensor 142 may include a current input port 141 and a current output port 143, as well as a standard ground 145, a common collector voltage (VCC) 146, and an output port 147. The current sensor 142 may also include a housing 148 comprising the polymer composition described above, which may accommodate other components of the current sensor 142, such as resistors, capacitors, converters, processing chips, etc.

[0105] Another component of an electric vehicle that may include the polymer composition is an inverter system, one exemplary embodiment of which is as follows: Figure 6As shown. The system includes an inverter module 320 and an interconnect system 335. The interconnect system 335 includes an electromagnetic interference (EMI) core 330 and an EMI filter device 325. The inverter module 320 is coupled to the interconnect system 335 via a pair of buses 310. The EMI core 330 is located between the EMI filter device 325 and the inverter module 320 and is connected to the bus 310. The EMI filter device 325 includes an EMI filter card 340 and a pair of bolts 350, 352, each including a positive (+) bolt 350 and a negative (−) bolt 352 for coupling to a power source, such as a battery assembly 124. The EMI core 330 is coupled to the bolts 350, 352 via the bus 310. The EMI filter card 340 is also coupled between ground and the bus 310 via a pair of wires 334. The inverter module 320 includes multiple transistors (not shown). The transistors in inverter module 320 turn on and off relatively quickly (e.g., from 5 kHz to 20 kHz). This switching often generates electrical switching noise. Ideally, this electrical switching noise should be contained within inverter module 320 and prevented from entering the rest of the electrical system to avoid interfering with other electrical components in the vehicle.

[0106] The inverter system may include several components that may incorporate the disclosed polymer composition, including but not limited to EMI filter 325 (e.g., as a housing and / or internal support structure), EMI filter card 340, bus 310, and connectors used within the system. For example, electrical connectors incorporating the polymer composition described herein can be used for... Figure 7 In the inverter system shown or in another part of an electric vehicle, the electrical connector typically includes a first connector portion containing at least one electrical contact and an insulating element surrounding at least a portion of the connector portion. The insulating element may comprise the polymer composition of the present invention. The first connector portion may be configured to mate with an opposing second connector portion, the second connector portion including a receptacle for receiving the electrical contact. In this embodiment, the second connector portion may include at least one receptacle configured to receive the electrical contact of the first connector portion and an insulating element surrounding at least a portion of the second connector portion. The insulating element of the second connector portion may also comprise the polymer composition of the present invention.

[0107] Reference Figure 7 , Figure 8 and Figure 9This illustration shows a specific embodiment of a connector 200 for an electric vehicle (e.g., an electric vehicle powertrain). The connector 200 includes a first connector portion 202 and a second connector portion 204. The first connector portion 202 may include one or more electrical pins 206, and the second connector portion 204 may include one or more sockets 208 for receiving the electrical pins 206. A first insulating member 212 may extend from the bottom 203 of the first connector portion 202 to surround the pins 206, and similarly, a second insulating member 218 may extend from the bottom 201 of the second connector portion 204 to surround the sockets 208. In some cases, the periphery of the first insulating member 212 may extend beyond the ends of the electrical pins 206, and the periphery of the second insulating member 218 may extend beyond the ends of the sockets 208. The bottom 203 of the first connector portion 202 and / or the first insulating member 212, and the bottom 201 of the second connector portion 204 and / or the second insulating member 218 may be formed from the polymer composition of the present invention.

[0108] While not strictly necessary, the first connector portion 202 may also include an identification mark 210, which is affixed to or defined by the first protector 212. The second connection portion 204 may also optionally define an alignment window 220, the size of which is determined by the identification mark 210, to more easily determine when the portions are fully aligned. For example, the identification mark 210 may be unreadable unless a barrier 221 covers a portion of it. Optionally, the second connection portion 204 may include a supplementary mark 224 immediately adjacent to the alignment window 220.

[0109] Figure 10 and Figure 11 Other embodiments of components that can use the polymer compositions of the present invention are shown, such as... Figure 10 The examples shown are gaskets, connectors, insulators, and supports that can be formed from polymer compositions. Figure 11 The components shown may include: quick connectors, tees, and interconnects, wherein multiple of them are in... Figure 11 The top shows a brushless DC motor ( Figure 11 (The middle left side), such as the motor's sealing ring, housing, support components, etc.; guide rail ( Figure 11 The right side of the middle section also shows other examples of the busbar in the image; and the battery sealing ring ( Figure 11 (Bottom)

[0110] Systems employing the polymer compositions of the present invention are by no means limited to electrical systems. For example, thermal management systems can also advantageously incorporate polymer compositions. Thermal management systems for electric vehicles typically include multiple distinct subsystems, such as, but not limited to, powertrain subsystems, refrigeration subsystems, battery cooling subsystems, and heating, ventilation, and cooling (HVAC) subsystems. In some embodiments, one or more subsystems of the thermal management system may be in fluid communication with each other, thereby allowing hotter heat transfer media to flow from high-temperature circuits to low-temperature circuits, and allowing colder heat transfer media to flow from low-temperature circuits to high-temperature circuits.

[0111] For example, Figure 12 This illustrates a first temperature control loop that can be seen in an electric vehicle. Figure 13 A second temperature control loop, as seen in electric vehicles, is illustrated. Each loop is designed for a different subsystem, and each loop includes one or more components that can employ the polymer compositions of the present invention. For example, a first temperature control loop in a typical electric vehicle ( Figure 12 The system may include a heat transfer medium (e.g., water) pumped through the loop by a suitable pump 160 (e.g., an electric water pump) and cooled by heat transfer with a heat exchanger 163 (e.g., an energy storage system (ESS) heat exchanger) and a refrigerant in a radiator / reservoir 164. Furthermore, the loop may include a heater 166 (e.g., a positive temperature coefficient (PTC) heater) and a battery assembly 124, which ensures that the system temperature remains within its preferred operating range regardless of ambient temperature. A second temperature control loop ( Figure 13 It may also include a heat transfer medium, which may be the same as or different from the heat transfer medium of another subsystem. The heat transfer medium of the second temperature control loop can be pumped through the loop by a suitable pump 161, heat exchanger 163, and radiator reservoir 165. The high-temperature control loop can be used to cool the vehicle's power electronics 167 and motor 114.

[0112] An example of a thermal management system component that may include the polymer composition of the present invention is a coolant pump, such as an electric water pump, examples of which are... Figure 14As shown, the electric water pump 401 includes an electric motor 410 as a drive source and a hydraulic section 420 for generating coolant suction and discharge forces. The motor 410 and related components are housed in a motor housing 411. The hydraulic section 420 includes a volute 421, which typically includes a helical flow space, an inlet 422, and an outlet 423, as well as an impeller (not shown) rotated by the electric motor 410. The pump 401 has an interface including a mechanical seal (not shown) for sealing and separating the water flow space from the motor chamber. Typically, a mounting portion 412 is provided on the motor housing 411 for mounting the pump 401 in a vehicle. Components of the electric pump 401 (e.g., housing, sleeve, interface, etc.) may contain the polymer composition of the present invention.

[0113] The present invention can be better understood by referring to the following embodiments.

[0114] Test methods

[0115] Melt viscosity: Melt viscosity (Pa-s) can be determined according to ISO 11443:2021 at 400s. -1 The shear rate was measured using a Dynisco LCR7001 capillary rheometer. The rheometer orifice (dial) could have a diameter of 1 mm, a length of 20 mm, an L / D ratio of 20.1, and an inlet angle of 180°. The cylinder diameter could be 9.55 mm ± 0.005 mm, and the rod length was 233.4 mm. Melt viscosity was typically measured at 310°C.

[0116] Tensile modulus, tensile stress at break, and tensile strain at break: Tensile properties can be tested according to ISO 527-2 / 1A:2019 (technically equivalent to ASTM D638-14). Modulus and strength measurements can be performed on identical test strips with a length of 80 mm, a thickness of 10 mm, and a width of 4 mm. The test temperature can be 23°C, and the test speed can be 5 mm / min.

[0117] Flexural modulus, breaking flexural stress, and flexural stress: Flexural properties can be tested according to ISO 178:2019 (technically equivalent to ASTM D790-10). This test can be performed over a 64 mm support span. The test can be performed on the center portion of an uncut ISO 3167 multipurpose bar. The test temperature can be 23°C, and the test speed can be 2 mm / min.

[0118] Simply supported beam impact strength: The performance of simply supported beams can be tested according to ISO 179-1:2010 (technically equivalent to ASTM D256-10, Method B). This test can be performed using a Type 1 specimen (80 mm in length, 10 mm in width, and 4 mm in thickness). When testing notched impact strength, the notch can be a Type A notch (0.25 mm base circle radius). The specimen can be cut from the center of a multi-purpose bar using a single-tooth milling machine. The test temperature can be 23°C.

[0119] Comparative Tracking Index (“CTI”): The Comparative Tracking Index (CTI) is determined according to the international standard IEC 60112-2003 to provide a quantitative indication of the performance of a composition as an electrical insulation material under wet and / or contaminated conditions. In determining the CTI rating of a composition, two electrodes are placed on a molded test specimen. A voltage difference is subsequently established between the electrodes when a 0.1% ammonium chloride aqueous solution is dropped onto the test specimen. The maximum voltage at which five (5) specimens withstand 50 drops of electrolyte without failure is determined over the test period. The test voltage range is from 100V to 600V in increments of 25V. The voltage at which failure occurs when fifty (50) drops of electrolyte are applied is the “Comparative Tracking Index”. This value provides an indication of the material’s relative resistance to tracking. According to UL 746A, a nominal part thickness of 3 mm is considered representative of performance at other thicknesses.

[0120] Flame retardancy: Flame retardancy can be determined according to the UL 94 vertical burning test procedure, “Test of flammability of plastic materials for parts of equipment and electrical appliances” (28 February 2023 edition), which is now consistent with IEC 60707, 60695-11-10 and 60695-11-20 and ISO 9772 and 9773. In the test, two groups of five samples (ten in total) can be used, with samples having a length of 125 mm, a width of 13 mm, and a thickness within the desired range (e.g., 0.2 mm, 0.4 mm, 0.8 mm or 1.5 mm). Both groups of samples can be conditioned before and after aging. For the unaged test, each thickness is tested after conditioning at 23°C and 50% relative humidity for 48 hours. For the aged test, five (5) samples of each thickness are tested after conditioning at 70°C for 168 hours and then cooling in a desiccator at room temperature for at least 4 hours. To begin testing, position the sample holder so that the sample is held at least 425 mm above the work surface. Place a cotton wadding (e.g., less than 6 mm thick) directly below the fixture to ensure coverage of a 50 mm × 50 mm area. Position the top 6 mm of the sample vertically in the fixture and adjust the holder so that the bottom edge of the sample is 300 ± 10 mm above the cotton wadding. Once in place, apply a flame for ten (10) seconds and then remove it until the flame stops. Apply the flame again for another ten (10) seconds and then remove it. If dripping occurs, it should fall onto the cotton wadding below the sample. Record the time when the flame stops burning as “t1”, and then apply the burner again. Record the time when the flame ends as “t2”. Record the time when incandescent burning ends as “t3”. Then compare the results with the UL94 flame retardancy rating based on the criteria provided in the table below.

[0121]

[0122] Thermal shock resistance: To test thermal shock resistance, first use Figures 15 to 18 The molds and inserts shown form four (4) types of sample parts. For example... Figure 15As shown, the first mold 100 is molded to produce a plastic thickness of 1.2 mm and a part size of 63.8 mm × 20 mm × 10.4 mm; the second mold 200 is molded to produce a plastic thickness of 2.5 mm and a part size of 65.1 mm × 22.6 mm × 13 mm; the third mold 300 is molded to produce a plastic thickness of 1.2 mm and a part size of 40 mm × 20 mm × 10.4 mm; and the fourth mold 400 is molded to produce a plastic thickness of 42.6 mm × 22.6 mm × 13 mm. Each of the molds 300 and 400 has two circular holes 402 formed on its cavity side, parallel to the longitudinal edge of the mold. The holes 402 have a diameter of 3.5 mm and are recessed into the cavity side of the mold. The first mold 100 and the second mold 200 respectively include metal inserts 105 and 205 (see...). Figure 16 Metal inserts 105 and 205 are formed from AISI H13 / 440C stainless steel sheets with dimensions of 62.6mm × 18mm × 18mm and are embedded in the mold without forming weld seams. Inserts 105 and 205 have a single circular hole 502 with a diameter of 5mm at their respective ends. The third mold 300 and the fourth mold 400 also contain metal inserts 305 and 405 respectively (see...). Figure 16 The metal inserts 305 and 405 are formed from AISI H13 / 440C stainless steel sheets with dimensions of 37.6mm × 18mm × 18mm. For example... Figure 16 As shown, each of the metal inserts 305 and 405 includes two circular holes 602, which are arranged parallel to the lateral edge of the insert and recessed into the core side of the respective insert. The diameter of the holes 602 is 2.0 mm and the depth of the recess into the core side of the insert is 5 mm. When embedded in the molds 300 and 400, a weld is formed at the line where the two flow fronts meet, preventing the flow fronts from being "woven" or "welded" together during the molding process.

[0123] Reference Figure 15 , Figure 17 and Figure 18The aforementioned mold can be used to form sample parts. First, the polymer composition is passed through a gate 702, which has an upper end 704 with a small diameter (i.e., 6 mm) and a lower end 706 with a diameter larger than the upper end 704 (i.e., 8 mm). The polymer composition flows through the gate 702 into a first runner 802 (7 mm in diameter), and through a gate 804 for a third mold 300 with dimensions of 0.8 mm × 10 mm, and through a gate 806 for a fourth mold 400 with dimensions of 1.7 mm × 10 mm. Similarly, the polymer composition flows through the gate 702 into a second runner 902 (6 mm in diameter), and through a gate 904 for a first mold 100 with dimensions of 0.8 mm × 10 mm, and through a gate 906 for a fourth mold 400 with dimensions of 1.7 mm × 10 mm. The draft angle on each side of the mold is 1.5°. When forming the molded part, the processing conditions can be selected according to methods known to those skilled in the art. For example, the melt temperature and nozzle temperature can be 320°C, the injection pressure can be 1250 bar, the peak pressure can be 1146 bar (e.g., for mold 100) and 1120 bar (e.g., for mold 300), the injection speed can be 80 mm / s and the injection time can be about 0.25 s, the holding pressure can be about 800 bar, the cooling time can be about 15 s, and the total cycle time can be about 23 s.

[0124] Each of the molds described above can be used to form a set of twenty (20) sample parts. The sample parts are then subjected to a first heating cycle in a thermal shock chamber with hot and cold zones, such as the thermal shock chamber available from Weisstechnik under the name "ShockEvent T / 120 / V2". The hot zone can be heated to a temperature of 140°C, and the cold zone can be cooled to a temperature of -40°C. To initiate the first heating cycle, the sample parts are placed in the hot zone for 30 minutes, and then the product carrier in the chamber moves the sample parts from the hot zone to the cold zone, where they are placed for another 30 minutes. In this way, the total time for the first cycle is 1 hour. 24 cycles are performed per day, each cycle lasting 1 hour. For the first two weeks, the cracking of the sample parts is visually observed once a day, and then twice a week, until all twenty (20) samples have cracked or a full set of cycles has been completed. A full set of cycles can be 1500 or 3000 cycles, depending on the test protocol. When the first sample cracks, the number of cycles reached before cracking is recorded as the "thermal shock resistance value". If a full set of cycles (1500 or 3000) is completed without any cracking of any sample, the "thermal shock resistance value" is simply recorded as ">1500" or ">3000", depending on the specific test protocol.

[0125] Comparative Example 1

[0126] Comparative Example 1 was melt-blended using a 32mm Coperion co-rotating fully intermeshing twin-screw extruder, containing various concentrations of polyarylene sulfide (PPS 2), impact modifier (impact modifier 2), glass fiber, siloxane polymer, organosilane compound, mineral particles 1, lubricant, and colorant. The melt flow index of PPS 2 was approximately 1000 g / 10 min. Impact modifier 2 was a random terpolymer of ethylene, acrylate, and glycidyl methacrylate, with glycidyl methacrylate comprising 7.25 wt.%. Mineral particles 1 were calcium carbonate particles with a median particle size of approximately 3.2 μm and a moisture content of less than 0.2%. The siloxane polymer was a UHMW-functionalized siloxane polymer, supplied as a masterbatch, with a siloxane content of 50% and a resin content of 50%. The organosilane compound was 3-aminopropyltriethoxysilane. The formulation is listed in more detail in the table below.

[0127]

[0128] After formation, the resulting composition was injection molded, and its properties were tested according to the methods described above. The results are listed in the table below.

[0129]

[0130] Examples 1-3

[0131] Examples 1 to 3 were melt-blended using a 32mm Coperion co-rotating twin-screw extruder, containing various concentrations of polyarylene sulfide (PPS 1), impact modifier (impact modifier 1), glass fiber, siloxane polymer, organosilane compound, mineral particles (mineral particles 1, 2, and 3), and colorant. PPS 1 had a melt flow index of approximately 500 g / 10 min. Impact modifier 1 was a random copolymer of ethylene and glycidyl methacrylate, with a glycidyl methacrylate content of 8 wt.% and a melt flow index of 5 g / 10 min at 190°C. Mineral particles 2 were ultrafine wollastonite particles with a median particle size of 2 μm. Mineral particles 3 were stearic acid-coated calcium carbonate particles with a median particle size of approximately 2.5 μm and a moisture content of less than 0.1%. The siloxane polymer and organosilane compound were the same as those used in Comparative Example 1. The formulations for each example are detailed in the table below.

[0132]

[0133] After formation, the resulting composition was injection molded, and its properties were tested according to the methods described above. The results are listed in the table below.

[0134]

[0135] Example 4

[0136] Example 5 used a 32mm Coperion co-rotating fully intermeshing twin-screw extruder for melt mixing, containing various concentrations of PPS 2, impact modifier 2, glass fiber, siloxane polymer, organosilane compound, mineral particles 4, and colorant. The siloxane polymer and organosilane compound were the same as those used in Examples 1-3. The formulation is detailed in the table below.

[0137]

[0138] After formation, the resulting composition was injection molded, and its properties were tested according to the methods described above. The results are listed in the table below.

[0139]

[0140] Example 5

[0141] Example 5 used a 32mm Coperion co-rotating fully intermeshing twin-screw extruder for melt mixing, containing various concentrations of PPS 2, impact modifier 1, glass fiber, siloxane polymer, organosilane compound, mineral particles 4, and colorant. The siloxane polymer and organosilane compound were the same as those used in Examples 1-3. The formulation is detailed in the table below.

[0142]

[0143] After formation, the resulting composition was injection molded, and its properties were tested according to the methods described above. The results are listed in the table below.

[0144]

[0145] Example 6

[0146] Example 6 used a 32mm Coperion co-rotating fully intermeshing twin-screw extruder for melt mixing, containing various concentrations of PPS 2, impact modifier 1, glass fiber, siloxane polymer, organosilane compound, mineral particles 3, and colorant. The siloxane polymer and organosilane compound were the same as those used in Examples 1-3. The formulation is detailed in the table below.

[0147]

[0148] After formation, the resulting composition was injection molded and its thermal shock resistance was tested. The thermal shock resistance value was 1,000.

[0149] Example 7

[0150] Example 7 used a 32mm Coperion co-rotating fully intermeshing twin-screw extruder for melt mixing, containing various concentrations of PPS 2, PPS 3, impact modifier 1, glass fiber, siloxane polymer, organosilane compound, mineral particles 3, and colorant. The melt flow index of PPS 3 was 500 g / 10 min, resulting in a total melt flow index of approximately 735 g / 10 min for the resulting polymer matrix. The siloxane polymer and organosilane compound were the same as those used in Examples 1-3. The formulation is detailed in the table below.

[0151]

[0152] After formation, the resulting composition was injection molded, and its properties were tested according to the methods described above. The results are listed in the table below.

[0153]

[0154] These and other modifications and variations can be made to the invention by those skilled in the art without departing from the spirit and scope of the invention. Furthermore, it should be understood that aspects of the various embodiments can be interchanged entirely or partially. In addition, those skilled in the art will understand that the foregoing description is merely exemplary and is not intended to limit the invention as further described in the appended claims. Claims (as amended under Article 19 of the Treaty) 1. A polymer composition comprising a polymer matrix, an impact modifier, mineral particles, and reinforcing fibers, wherein the impact modifier, mineral particles, and reinforcing fibers are dispersed in the polymer matrix, wherein the polymer matrix comprises a polyarylene sulfide and exhibits a melt flow index of about 500 to about 1,000 g / 10 min as determined according to ASTM D1238-13 at a load of 2.16 kg and a temperature of 190°C, wherein the weight ratio of the reinforcing fibers to the mineral particles is about 2 or greater, and wherein the polymer composition also exhibits a thermal shock resistance value of about 800 or higher. 2. The polymer composition according to claim 1, wherein the mineral particles comprise calcium carbonate particles. 3. The polymer composition according to claim 1, wherein the mineral particles contain a surface treatment agent. 4. The polymer composition according to claim 3, wherein the surface treatment agent contains fatty acids. 5. The polymer composition of claim 1, wherein the median particle size of the mineral particles is about 0.5 to about 10 micrometers. 6. The polymer composition according to claim 1, wherein the moisture content of the mineral particles is about 0.5% or less. 7. The polymer composition according to claim 1, wherein the reinforcing fiber comprises glass fiber. 8. The polymer composition of claim 1, wherein the reinforcing fibers are present in an amount of about 50 to about 150 parts by weight per 100 parts by weight of the polymer matrix, and the mineral particles are present in an amount of about 10 to about 50 parts by weight per 100 parts by weight of the polymer matrix. 9. The polymer composition according to claim 1 further comprises an ultra-high molecular weight siloxane polymer with a weight-average molecular weight of about 100,000 g / mol or greater. 10. The polymer composition according to claim 1, further comprising an organosilane compound. 11. The polymer composition of claim 1, wherein the impact modifier is present in an amount of about 1 to about 30 parts by weight per 100 parts by weight of the polymer matrix. 12. The polymer composition of claim 1, wherein the impact modifier comprises an epoxy functionalized monomer unit. 13. The polymer composition of claim 1, wherein the polymer matrix comprises about 10 wt.% to about 70 wt.% of the polymer composition. 14. The polymer composition of claim 1, wherein the polymer matrix comprises a first polyarylene sulfide and a second polyarylene sulfide, wherein the ratio of the melt flow index of the first polyarylene sulfide to the melt flow index of the second polyarylene sulfide is from about 1.5 to about 3. 15. The polymer composition of claim 1, wherein the polymer composition exhibits a V-0 rating as determined by UL94 testing at a thickness of 1.5 mm. 16. A composite structure comprising a metal component and a resin component, the metal component being in contact with the resin component, the resin component comprising the polymer composition according to claim 1. 17. An electric vehicle comprising a power system including at least one electric propulsion source and a transmission connected to the propulsion source via at least one power electronic module, wherein the electric vehicle comprises the composite structure according to claim 16. 18. The electric vehicle of claim 17, wherein the electric vehicle includes electrical components comprising the composite structure. 19. The electric vehicle of claim 18, wherein the electrical components include a busbar, a current sensor, an inverter filter, an electrical connector, a brushless DC motor, a guide ring, a battery cell sealing ring, or a combination thereof. 20. The electric vehicle of claim 17, wherein the electric vehicle includes a thermal management system component comprising the polymer composition.

Claims

1. A polymer composition comprising a polymer matrix, an impact modifier, mineral particles, and reinforcing fibers, wherein the impact modifier, mineral particles, and reinforcing fibers are dispersed in the polymer matrix, wherein, The polymer matrix comprises polyarylene sulfide and exhibits a melt flow index of about 500 to about 1,000 g / 10 min as determined by ASTM D1238-13 at a load of 2.16 kg and a temperature of 190 °C, wherein the weight ratio of the reinforcing fiber to the mineral particles is about 2 or greater, and wherein the polymer composition also exhibits a thermal shock resistance value of about 800 or higher.

2. The polymer composition according to claim 1, wherein the mineral particles comprise calcium carbonate particles.

3. The polymer composition according to claim 1, wherein the mineral particles contain a surface treatment agent.

4. The polymer composition according to claim 3, wherein the surface treatment agent contains fatty acids.

5. The polymer composition of claim 1, wherein the median particle size of the mineral particles is about 0.5 to about 10 micrometers.

6. The polymer composition according to claim 1, wherein the moisture content of the mineral particles is about 0.5% or less.

7. The polymer composition according to claim 1, wherein the reinforcing fiber comprises glass fiber.

8. The polymer composition of claim 1, wherein the reinforcing fibers are present in an amount of about 50 to about 150 parts by weight per 100 parts by weight of the polymer matrix, and the mineral particles are present in an amount of about 10 to about 50 parts by weight per 100 parts by weight of the polymer matrix.

9. The polymer composition according to claim 1 further comprises an ultra-high molecular weight siloxane polymer with a weight-average molecular weight of about 100,000 g / mol or greater.

10. The polymer composition according to claim 1, further comprising an organosilane compound.

11. The polymer composition of claim 1, wherein the impact modifier is present in an amount of about 1 to about 30 parts by weight per 100 parts by weight of the polymer matrix.

12. The polymer composition of claim 1, wherein the impact modifier comprises an epoxy functionalized monomer unit.

13. The polymer composition of claim 1, wherein the polymer matrix comprises about 10 wt.% to about 70 wt.% of the polymer composition.

14. The polymer composition of claim 1, wherein the polymer matrix comprises a first polyarylene sulfide and a second polyarylene sulfide, wherein the ratio of the melt flow index of the first polyarylene sulfide to the melt flow index of the second polyarylene sulfide is from about 1.5 to about 3.

15. The polymer composition according to claim 1, wherein, The polymer composition exhibits a V-0 rating as determined by UL94 testing at a thickness of 1.5 mm.

16. A composite structure comprising a metal component and a resin component, the metal component being in contact with the resin component, the resin component comprising the polymer composition according to claim 1.

17. An electric vehicle comprising a power system, the power system including at least one electric propulsion source and a transmission device connected to the propulsion source via at least one power electronic module, wherein, The electric vehicle includes the composite structure according to claim 15.

18. The electric vehicle according to claim 17, wherein, The electric vehicle includes electrical components incorporating the composite structure.

19. The electric vehicle according to claim 18, wherein, The electrical components include busbars, current sensors, inverter filters, electrical connectors, brushless DC motors, guide rings, battery cell sealing rings, or combinations thereof.

20. The electric vehicle according to claim 17, wherein, The electric vehicle includes a thermal management system component comprising the polymer composition.

Citation Information

Patent Citations

  • Ultra-high molecular weight, soluble siloxane resins

    US6072012A